Implementation of Legal Aid to Debtors Due to Arrears in Motor Vehicle Installments Executed by Debt Collectors as Impact of the Covid-19 Pandemic - Sulistyowati, Widya Kurnia (The Indonesian Journal of International Clinical Legal Education, 2021)
Based on Law No. 16 of 2011 on Legal Aid, Article 1 paragraph (1) states that Legal Aid is a legal service provided by legal aid providers free of charge to Legal Aid Recipients. Legal aid is a guarantee of legal protection and a guarantee of equality before the law, which is a constitutional right for every citizen. Because, the constitution guarantees the right of every citizen to get equal treatment before the law, including the right to access justice through legal aid. Due to the Covid-19 pandemic, many people are asking for legal assistance related to the case of installment billing by debt collectors. The debt collector itself is a third party, which has an agreement with the financing institution to make efforts to force the collection of debtor vehicles because it has not paid installments as agreed. The result of this paper is that under these circumstances there is another legal remedy, namely restructuring.